Analisis User Experience Aplikasi Mobile Facebook (Studi Kasus pada Mahasiswa Universitas Brawijaya) - Rio Donaroe Munthe; Komang Candra Brata; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In 2003, Steve Jobs criticized common understanding of user experience design (UXD). Instead of the thought that a design is something we can see and fell, he proposed that design is not just what it looks and feels like, it's how it works. Frank Guo simplified the concept by dividing into four elements: value, adoptability, desirability, & usability (VADU). The UX concept is adopted by various social media platforms, including Facebook. The Facebook mobile app has repeatedly changed to improve the user experience. This study identified the UX concept on Facebook. It can be an example for developers who want to develop similar applications. Questions for respondents are arranged based on 4 fundamental variables UX (VADU) in Likert Scale. The research method used is the validity & reliability test. The questionnaire results are elaborated by descriptive analysis based on UX variables. In the end, to know the most important element of UX is used "YES & NO" method. Based on the results, the features are important to increase the value. In adoptability, the ease to access is a concern. An attractive visual design is the main indicator in the desirability. And, the easy-to-learn is the key thing for the usability.